Analysis Factors Related to Behaviour among Madurese Mothers with Exclusive Breastfeeding - Taqiyatul Izzah; Mira Triharini; Retnanyu Pradanie (Pediomaternal Nursing Journal, 2021)
Introduction: The rate of exclusive breastfeeding in Indonesia is still low. Internal and external factors mother can cause a low rate of exclusive breastfeeding. This also happens because of the belief and traditional factors that can inhibit exclusive breastfeeding for babies. This study aimed to analyze the correlation of psychological factors, family support, and socio-culture with the behaviour of Madurese ethnic mothers in exclusive breastfeeding.Methods: This study used descriptive-analytical with a cross-sectional approach. The research sample collected 100 respondents with nonprobability sampling method is purposive sampling.Results: There was a moderate correlation between family support (p= 0.000; r = 0.373) and socio-culture (p= 0.000; r = 0.396) with the behaviour of Madurese ethnic mothers in exclusive breastfeeding. The analysis showed no relation between psychological factors and the behaviour of Madurese ethnic mothers in exclusive breastfeeding (p=0.071; r= 0.181).Conclusion: The Behaviour of Madurese ethnic mothers in exclusive breastfeeding in The Sidotopo Wetan Community Health Center, Surabaya, was related to family support and socio-culture. So, the research can be used as this information to optimize factors that increase exclusive breastfeeding behaviour.